2011
DOI: 10.1016/j.foodchem.2010.12.035
|View full text |Cite
|
Sign up to set email alerts
|

In vivo antitumoural activity and composition of an oil extract of Brazilian propolis

Abstract: The present study aimed to evaluate in vivo and in vitro the antitumoural activity of a propolis extract obtained with edible vegetable oil and its fractions and also to investigate its chemical composition by LC-MS and LC-MS/MS. To evaluate the toxicological aspects related to the propolis extract treatment, hematological, biochemical, histopathological and morphological analyses of treated animals were performed. All propolis extracts showed an in vivo antitumour activity in the experimental model with a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 24 publications
1
42
0
7
Order By: Relevance
“…Thus, evaluating the pharmacological actions of these compounds in complete biological systems becomes an obligatory requirement. In order to assess the in vivo antitumoral action, the compounds were evaluated using the Sarcoma 180 experimental model, a mouse-derived tumor widely exploited in antitumor research [20,[38][39][40]. In Sarcoma-180-bearing animal assays, only thalidomide and compounds It has been demonstrated that inhibition of angiogenesis and tumor growth by thalidomide or analogues requires metabolic activation [12,[41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, evaluating the pharmacological actions of these compounds in complete biological systems becomes an obligatory requirement. In order to assess the in vivo antitumoral action, the compounds were evaluated using the Sarcoma 180 experimental model, a mouse-derived tumor widely exploited in antitumor research [20,[38][39][40]. In Sarcoma-180-bearing animal assays, only thalidomide and compounds It has been demonstrated that inhibition of angiogenesis and tumor growth by thalidomide or analogues requires metabolic activation [12,[41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…The name propolis is used to describe a complex mixture of resinous, gummous and balsamic substances collected by honey bees from plant sprouts, flowers and exudates, to which bees add saliva, wax, and pollen to elaborate the final product (Ghisalberti, 1979). Countless biological properties have been associated with propolis, such as antibacterial, antifungal, anti-inflammatory, antitumor, and antioxidant actions (Carvalho et al, 2011;Chaillou & Nazareno, 2009;Kalogeropoulos et al, 2009;Paulino et al, 2008). However, in spite of the antimicrobial properties, the use of propolis in foods is still limited, mainly because of its strong and characteristic flavor which may alter sensory characteristics of the foods.…”
Section: Introductionmentioning
confidence: 99%
“…Bees use propolis in their combs as protection, to repair damage, to build aseptic locals and as a thermal insulator (Cardoso et al, 2011). Many studies have reported the efficiency of this product in medical treatments, both human and animal (Pastor et al, 2010;Carvalho et al, 2011). However, these studies have focused mainly the bioactive compounds' analysis and performed clinical assays, in order to ascertain the properties of this beehive product.…”
Section: Introductionmentioning
confidence: 99%